Institutionsweite Hochschulentwicklung zur nachhaltigen Gestaltung von Lehr-/Lernkulturen - Jenert, Tobias; Brahm, Taiga

Programmentwicklung zur nachhaltigen Qualitätsentwicklung von Studiengängen - Brahm, Taiga; Jenert, Tobias
Keywords: Hochschulentwicklung

Besseres Feedback, mehr Reflexion? Fertigkeiten und Einstellungen Studierender zum Bloggen in Praxisprojekten - Jenert, Tobias; Gebhardt , Anja (Wissensgemeinschaften. Digitale Medien - Öffnung und Offenheit in Forschung und Lehre)

Konsistente Gestaltung von Selbstlernumgebungen - Jenert, Tobias; Zellweger, Franziska (Kompetenzorientierte Hochschullehre: Die Notwendigkeit von Kohärenz zwischen Lernzielen, Prüfungsformen und Lehr-Lern-Methoden)

Planung und Organisation -Technologieeinsatz von der Bedarfsanalyse bis zur Evaluation - Jenert, Tobias; Brahm, Taiga (Lehrbuch für Lernen und Lehren mit Technologien)

QualiAss - ein Werkzeug zur Prozess- und Qualitätsunterstützung für schriftliche Prüfungen an Hochschulen : Nutzungsszenarien - Spezifikation - Einführung - Jenert, Tobias; Meier, Christoph; Brahm, Taiga (Wissensgemeinschaften: Digitale Medien, Öffnung und Offenheit in Forschung und Lehre)

Vibrational properties of the LiNbO3 z-surfaces - Sanna, S.; Berth, Gerhard; Hahn, W.; Widhalm, A.; Zrenner, Artur; Schmidt, W. G. (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control)
The existence of localized vibrational modes both at the positive and at the negative LiNbO3 (0001) surface is demonstrated by means of first-principles calculations and Raman spectroscopy measurements. First, the phonon modes of the crystal bulk and of the (0001) surface are calculated within the density functional theory. In a second step, the Raman spectra of LiNbO3 bulk and of the two surfaces are measured. The phonon modes localized at the two surfaces are found to be substantially different, and are also found to differ from the bulk modes. The calculated and measured frequencies are in agreement within the error of the method. Raman spectroscopy is shown to be sensitive to differences between bulk and surface and between positive and negative surface. It represents therefore an alternative method to determine the surface polarity, which does not exploit the pyroelectric or piezoelectric properties of the material.

In situ characterization of ZnTe epilayer irradiation via time-resolved and power-density-dependent Raman spectroscopy - Wiedemeier, V; Berth, Gerhard; Zrenner, Artur; Larramendi, E M; Woggon, U; Lischka, K; Schikora, D (Semiconductor Science and Technology)
Laser irradiation damage in ZnTe epilayers was analyzed in situ by power-density-dependent and time-resolved micro-Raman spectroscopy. Damage by ablation or compound decomposition on the sample surface was revealed by the decrease of the ZnTe–nLO mode intensity with the increase of laser power density. The appearance of the peaks associated with the stronger crystalline-tellurium modes, tellurium aggregates and second-order Raman scattering at room temperature μ-Raman spectra was observed for higher power densities than 4.4 × 105 W cm−2. The Raman signal time transients of ZnTe–nLO and crystalline-tellurium modes reveal an exponential evolution of the laser irradiation damage and a fast formation of crystalline tellurium aggregates on the layer surface.

Characterization of SiON integrated waveguides via FTIR and AFM measurements - Frers, Torsten; Hett, Thomas; Hilleringmann, Ulrich; Berth, Gerhard; Widhalm, Alex; Zrenner, Artur (2011 Semiconductor Conference Dresden)
Silicon oxynitride (SiON) layers for telecommunication device application are grown by Plasma Enhanced Chemical Vapor Deposition (PECVD) for various gas compositions of SiH4, N2O and NH3. Processing and annealing effects on the oxynitride films were studied by Fourier Transform Infrared Spectroscopy (FTIR) and Atomic Force Microscopy (AFM) measurements. By reduction of the silane (SiH4) gas flow and enhancement of the PECVD deposition temperature, the absorption loss due to NH bands can be nearly completely erased. Furthermore the surface roughness can be reduced by decreasing the gas flow and rising the deposition temperature. First waveguide structures are introduced and their characterization is presented.

Besseres Feedback, mehr Reflexion? – Fertigkeiten und Einstellungen Studierender zum Bloggen in Praxisprojekten - Jenert, Tobias; Gebhardt , Anja (Wissensgemeinschaften : Digitale Medien - Öffnung und Offenheit in Forschung und Lehre)
Der Beitrag untersucht die Weblog-Arbeit Studierender zur Dokumenta¬tion und Reflexion von Praxisprojekten. Zu Beginn und nach Abschluss einer Lehrveranstaltung mit Praxisphase wurden Studierende zum Weblog-Arbeit befragt. Es zeigt sich, dass die Studierenden kaum über Erfahrungen in der Nutzung von Weblogs verfügen und überwiegend negative Einstellungen zum Bloggen aufweisen. Die Blogeinträge erreichen nicht die angestrebte Reflexionstiefe. Es wird diskutiert, wie das didaktische Design gestaltet werden kann, um die gewünschten Effekte - Peer-Feedback und tiefgehende Reflexion - zu erreichen.
Keywords: Weblogs; Selbststudium; Praxisprojekte; Hochschule; Edublog

Short- and long-term impact of remarkable economic events on the growth causes of China–Germany trade in agri-food products - Guo, Zhichao; Feng, Yuanhua; Tan, Xiangyong (Economic Modelling)

A blueprint for event-driven business activity management - Janiesch, Christian; Matzner, Martin; Müller, Oliver (Lecture Notes in Computer Science)
Keywords: Reference architecture; business activity management; business process analytics; business process management; complex event processing

Leaving the Beaten Tracks in Creative Work – A Design Theory for Systems that Support Convergent and Divergent Thinking - Müller-Wienbergen, Felix; Müller, Oliver; Seidel, Stefan; Becker, Jörg (Journal of the Association for Information Systems)
Keywords: Creativity; Creativity Support Systems; convergent thinking; design theory; divergent thinking

Walk your talk: an experimental investigation of the relationship between word of mouth and communicators’ loyalty - Garnefeld, Ina; Helm, Sabrina; Eggert, Andreas (Journal of Service Research)

Industrial services, product innovations, and firm profitability: A multiple-group latent growth curve analysis - Eggert, Andreas; Hogreve, Jens; Ulaga, Wolfgang; Muenkhoff, Eva (Industrial Marketing Management)

Exploring the Impact of Sales Technology on Salesperson Performance: A Task-Base d Approach - Eggert, Andreas; Serdaroglu, Murat (Journal of Marketing Theory and Practice)

Who follows the crowd—Groups or individuals? - Fahr, René; Irlenbusch, Bernd (Journal of Economic Behavior & Organization)

Job design and job satisfaction—empirical evidence for Germany? - Fahr, René (management revue)

When the early bird catches the worm: The impact of training in retail - Hinerasky, Christiane; Fahr, Rene

Key Account Management - Ivens, Björn; Eggert, Andreas (Handbuch Vertriebsmanagement)